2014
DOI: 10.1016/j.immuni.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor IRF8 Activates Integrin-Mediated TGF-β Signaling and Promotes Neuroinflammation

Abstract: SUMMARY Recent epidemiological studies have identified interferon regulatory factor 8 (IRF8) as a susceptibility factor for multiple sclerosis (MS). However, how IRF8 influences the neuroinflammatory disease has remained unknown. By studying the role of IRF8 in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, we found that Irf8−/− mice are resistant to EAE. Furthermore, expression of IRF8 in antigen presenting cells (APCs, such as macrophages, dendritic cells and microglia), but not in T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 50 publications
(100 reference statements)
7
107
0
1
Order By: Relevance
“…Neuroinflammation constitutes a fundamental process involved in the physiopathology of neurodegenerative disorders, including Parkinson's disease (PD) (Barcia et al 2012), Alzheimer's disease (AD) (Yoshiyama et al 2007), amyotrophic lateral sclerosis (ALS) (Frakes et al 2014) and multiple sclerosis (MS) (Yoshida et al 2014). Microglial cells play a central role in neuroinflammation, and thereby the functional phenotype acquired by these cells determines whether surrounding neurons survive or die.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation constitutes a fundamental process involved in the physiopathology of neurodegenerative disorders, including Parkinson's disease (PD) (Barcia et al 2012), Alzheimer's disease (AD) (Yoshiyama et al 2007), amyotrophic lateral sclerosis (ALS) (Frakes et al 2014) and multiple sclerosis (MS) (Yoshida et al 2014). Microglial cells play a central role in neuroinflammation, and thereby the functional phenotype acquired by these cells determines whether surrounding neurons survive or die.…”
Section: Introductionmentioning
confidence: 99%
“…The IRF8-GFP chimera protein is as functional as untagged IRF8, 38 and the knock-in mice showed no abnormality in hematopoiesis. 26,39 Somewhat unexpectedly, IRF8 expression, judged by GFP intensity, was not detectable in basophils in the bone marrow, spleen, and peripheral blood, or in mast cells in the peritoneal cavity, although it was abundant in B cells ( Figure 3A). Neutrophils and eosinophils did not express IRF8 either, consistent with previous reports.…”
Section: Resultsmentioning
confidence: 93%
“…BMP7 signaling was reported to play a critical role in LC development (11). A recent study (13) (14) recently reported that Irf8 expression leads to an increase in Id2 transcript levels. These findings suggest that Irf8 may play an important role in controlling TGF-b signaling in DCs.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-b1 was reported to upregulate Irf8 during DC development (12). Irf8 was shown to enhance transcription of Itgb8 gene that converts latent TGF-b to the active form at the interface of APCs and naive T cells (13). We analyzed the role of Irf8 in the regulation of TGF-b/BMP signaling in DCs using a commercially available PCR-based array specific to mouse TGFb/BMP signaling pathway genes.…”
mentioning
confidence: 99%